NILAI-NILAI BUDAYA DALAM TRADISI MANGAIN MASYARAKAT BATAK TOBA DI KELURAHAN TUK-TUK SIADONG :KAJIAN ANTROPOLOGI SASTRA - Tunggul Hamonangan Malau; Hera Chairunisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the cultural values ​​in the Mangain tradition of the Toba Batak people through traditional utterances spoken during the Mangain ceremony. The analysis was conducted using Edward Djamaris's theory of cultural values ​​to uncover the messages contained in the utterances. This study is a qualitative study with a descriptive approach that aims to systematically describe the facts and phenomena found in the field. The data collection technique used is the interview technique, which was chosen to obtain in-depth and comprehensive data. In its implementation, the researcher interviewed three sources, namely traditional leaders, community elders, and individuals who had been directly involved in the Mangain tradition. The results of the study indicate that the Mangain tradition contains various cultural values, including cultural values ​​in the relationship between humans and God, the relationship between humans and nature, the relationship between humans and society, the relationship between humans and other humans, and the relationship between humans and themselves.